Multisite evaluations of a T2‐relaxation‐under‐spin‐tagging (TRUST) MRI technique to measure brain oxygenation. Issue 2 (4th April 2015) - Liu, Peiying; Dimitrov, Ivan; Andrews, Trevor; Crane, David E.; Dariotis, Jacinda K.; Desmond, John; Dumas, Julie; Gilbert, Guillaume; Kumar, Anand; Maclntosh, Bradley J.; Tucholka, Alan; Yang, Shaolin; et al.
Abstract : Purpose: Venous oxygenation (Yv ) is an important index of brain physiology and may be indicative of brain diseases. A T2 ‐relaxation‐under‐spin‐tagging (TRUST) MRI technique was recently developed to measure Yv . A multisite evaluation of this technique would be an important step toward broader availability and potential clinical utilizations of Yv measures. Methods: TRUST MRI was performed on a total of 250 healthy subjects, 125 from the developer's site and 25 each from five other sites. All sites were equipped with a 3 Tesla (T) MRI of the same vendor. The estimated Yv and the standard error (SE) of the estimation εYv were compared across sites. Results: The averaged Yv and εYv across six sites were 61.1% ± 1.4% and 1.3% ± 0.2%, respectively. Multivariate regression analysis showed that the estimated Yv was dependent on age ( P  = 0.009) but not on performance site. In contrast, the SE of the Yv estimation was site‐dependent ( P  = 0.024) but was less than 1.5%. Further analysis revealed that εYv was positively associated with the amount of subject motion ( P  < 0.001) but negatively associated with blood signal intensity ( P  < 0.001). Conclusion: This work suggests that TRUST MRI can yield equivalent results of Yv estimation across different sites. Magn Reson Med 75:680–687, 2016. © 2015 Wiley Periodicals, Inc.